Appreciation family support and the abilities of children with special needs to maintain personal hygiene: an Indonesian case study - Ita Pursitasari; Allenidekania Allenidekania; Nur Agustini (MDPI AG, 2020)
Family support is needed to empower children with special needs to maintain personal hygiene, includes information, instrumental, emotional, and appreciation support. The study design was cross-sectional, involving 84 parents of children with special needs. The study was conducted via the respondents filling out a questionnaire consisting of three sub-questionnaires. The results showed no relationship between the characteristics of children with special needs and personal hygiene; there was also no relationship between parental characteristics and personal hygiene (P>0.05). There was, however, a relationship between information, instrumental, emotional, and appreciation support and personal hygiene (P<0.005), the most influential support being appreciation support. In conclusion, there was a significant relationship between information, instrumental, emotional, and appreciation support and the ability of children with special needs to maintain their personal hygiene. The recommendations for future studies are different research methods to explore more about the types of family support.